PENGATURAN INTERAKSI PROSES PENYIDIKAN DAN PENUNTUTAN DALAM SISTEM PERADILAN PIDANA DI INDONESIA - ZAINAB OMPU JAINAH (Universitas Bandar Lampung (UBL), 2018)
The enactment of Criminal Procedure Code as part of Criminal Law Policy with Law Number 8 Year 1981, in order to fulfill the provision that ensures law enforcement in accordance with their respective functions and authorities began to show limitations in achieving the objectives of the criminal justice process in Indonesia. Problems arise, among others, starting from the interaction of investigation and prosecution in Pre Prosecution. The problem of this research is the criminal law policy that regulates the interaction of investigation and prosecution process in the criminal justice system based on Law No. 8 of 1981 on Criminal Procedure Law. The research method used is the normative juridical approach of data consisting of secondary data and primary data. Data analysis is descriptive analysis. The results of the study showed that the disagreements in the investigation and prosecution process resulted in the back of the file. The formulation of Article relating to the process of interaction of investigation and prosecution in the Draft Law on Criminal Procedure is still formulated in a limitative manner, and has not had sufficient article explanation and has not been in line with international standard of good judicial process. The advice given is the need to be re-set clearly and firmly about the interaction of investigation and prosecution with the formulation of articles that are not multi-interpretation. Suggestions for notification of commencement of the investigation shall be obligations carried out no later than two days after the commencement of the investigation, and coordination and consultation shall commence from the commencement of the investigation.